Effectiveness of the current promotion strategies on Takaful Hawa Plan: Takaful Malaysia Berhad, Malacca Branch / Norliza Ismail - Ismail, Norliza (2004)
The major functions of Takaful Malaysia are to provide Islamic insurance to customers either their Muslims or Non-Muslims. With such objectives, Takaful Malaysia is highly determined provided the services in respect of the award cover the issuance of takaful certificate (policy) and the processing of claims for both takaful businesses. Therefore, the aim of this research is to measure the level of effectiveness of current promotion strategies on Takaful Hawa Plan. In order to complete this research, there are several limitations that were faced such as limited time, data accuracy, financial constraints and also lack of cooperation from the respondents. From the finding, in conclusion, majority of the respondent (customers) is satisfied with the current promotion performance where emphasize on personal selling. Therefore, Takaful Malaysia should improve their current promotion in order to satisfy their customers. This is an important way to make the image of Takaful Malaysia well established in the eyes of world.